PEMBELAJARAN PENDIDIKAN AGAMA HINDU BERBASIS AJARAN TRI RNA DALAM MEMBENTUK KARAKTER SISWA KELAS VI DI SD NEGERI 4 TEMUKUS, KECAMATAN BANJAR KABUPATEN BULELENG (JURDIKSCA: Jurnal Pendidikan Agama Hindu Mahasiswa Pascasarjana, 2025)
ABSTRACT Learning based on Tri Rna teachings in Hindu religious education is vital for fostering noble character in children, especially amid the declining interest in education caused by insufficient parental supervision and monotonous school activities. This study focuses on 6thgrade students at SD Negeri 4 Temukus, implementing innovative methods to restore motivation. The approach combines teaching Tri Rna theory covering obligations to God, teachers, and society—with practical applications in daily school routines, both before and after class hours. The research examines three key questions: (1) How is Tri Rna-based Hindu Religious Education implemented to shape students’ character? (2) What character values in Tri Rna-based learning contribute to this development? (3) What are the implications of this learning approach for character building? Guided by Behaviorism, Social Learning, and Learning Motivation theories, the study employs qualitative research with descriptive analysis and an experimental approach, positioning the researcher as the primary instrument.Data is collected using triangulation methods, including field observations, in-depth interviews with teachers and students, and document analysis. Informants are purposively selected based on their involvement in the study. The findings indicate that methods such as demonstrations, discussions, question-and-answer sessions, and evaluations effectively enhance learning outcomes. These methods positively impact students' attitudes, fostering respect for parents, teachers, peers, and promoting social and religious values. This success highlights the potential for broader implementation of Tri Rna teachings in other classes, reinforcing positive character formation and enhancing students’ educational experiences.
Keywords: Keywords: Implementation, Tri Rna, Hindu Religious Education, Student Character